Child Abuse Pediatricians Assess a Low Likelihood of Abuse in Half of 2890 Physical Abuse Consults. (May 2022) - Johnson, Katie L.; Brown, Emily C. B.; Feldman, Kenneth W.; Qu, Pingping; Lindberg, Daniel M.; ,
The aim of this study was to examine the frequency with which child abuse pediatricians (CAPs) assess consultations as low versus high likelihood of abuse. In this retrospective secondary analysis of data from the Examining Siblings to Recognize Abuse (ExSTRA) study, the likelihood of abuse score for 2890 consultations at 20 medical centers was collected. Descriptive statistics were used to examine the percentage of cases representing low versus high likelihood of abuse (i.e., score of 1–4 vs. 5–7 on a 7-point scale). Linear and logistic regression analyses were used to examine score variability between medical centers. Overall, fifty-three percent of cases were assessed as low likelihood of abuse, suggesting that CAPs were equally as likely to assess a high versus low likelihood of abuse. The percentage of cases representing low likelihood of abuse differed significantly ( P < .001) between medical centers after controlling for patient age, sex, race/ethnicity, twin/triplet status, injury types, and injury severity. The variability between CAP assessments at different medical centers is discussed, along with potential contributors to this variability and directions for future work.